SISTEM INFORMASI KESEHATAN BERBASIS WEB: SOLUSI UNTUK PENYEBARAN INFORMASI KESEHATAN DI MASYARAKAT DESA MOUTONG TENGAH - Toar. W. J. Hatibie; Nadiya Pakaya; Ristian Bakari (Journal of Hulonthalo Service Society (JHSS), 2024)
In the digital era, information technology has become an important tool to support the dissemination of information, including in the health sector. This article aims to describe the development and implementation of a web-based health information system in Central Moutong Village. This system is designed to provide easy access to health information to village communities, including information about health services, doctor's visit schedules, and health education. The research method used is community service through a participatory approach that actively involves villagers. The results show that the implementation of this system increases community knowledge about health and access to health services.